Interannual variation of coastal upwelling around Hainan Island - Zhu, Junying; Zhou, Quanyi; Zhou, Qianqing; Geng, Xinxing; Shi, Jie; Guo, Xinyu; Yu, Yang; Yang, Ziwei; Fan, Renfu (Frontiers in Marine Science, 2023)
Coastal upwelling around Hainan Island has a significant impact on the physical environment, ecological environment, and fishery resources of the surrounding waters. Based on the satellite-observed sea surface temperature (SST) from 2003 to 2021, this study analyzed the interannual variations of SST around Hainan Island and the influence of the sea surface forcing on them, with special attention to the upwelling regions in Qiongdong and Qiongxi. The results show that satellite-observed SST can identify three upwelling regions located in the west (WS), east (ES), and northeast (NES) sides of the Hainan Island. The SSTs in the WS, ES, and NES showed warming trends of 0.045 °C/y, 0.010 °C/y, and 0.036 °C/y, respectively. The range of low-temperature water around Hainan Island has gradually shrunk over the past two decades, and this shrinkage trend was more prominent in the WS upwelling region than in the ES and NES upwelling regions. Both the EOF analysis and the SST difference between upwelling regions and non-upwelling regions suggests that the upwelling becomes stronger after 2013. However, it seems not to compete with the overall SST warming in the northwest area of the South China Sea. The interannual SST variations in the ES upwelling region were affected by the local wind stress curl in summer. Except for the wind stress curl, the interannual SST variations in NES upwelling are influenced by the stratification associated with local precipitation and wind direction, especially in 2018. In addition, the interannual SST variation in the WS upwelling region is closely related to the bottom cold water in the central Gulf of Tonkin, which was preserved from the previous winter and is influenced by winter atmospheric conditions. These results are helpful for understanding the variations in SST and ecosystem in the upwelling regions around Hainan Island.